MEMBUMIKAN AKAD MUDHARABAH DALAM PRAKTEK PERBANKAN SYARI’AH - Qomar, Moh Nurul (Fakultas Ekonomi, UIN Maliki Malang, 2014)
The present study aimed at finding mudaraba position in the middle of the fiqh literature and Shariahbanking, so employing qualitative approach and patterned library research. Mudaraba is a business cooperationcontract as between two parties, where the first (Shahibul mall) provides the capital, while others becamemanager. Because that’s the nature of mudaraba more practical to run on Islamic banking compared withshirkah. Mudharabah was not the original products of Islamic law. Mudaraba has been practiced long beforeMohammed became a prophet. The acceptance of mudaraba as part mu’amalah rule in Islam, because there isno description of the scholars of fiqh which prohibit.